Uji Cemaran Mikroba Pada Air Yang Digunakan Untuk Mencuci Peralatan Makan Oleh Pedagang Kaki Lima di Sekitar UIN Sunan Ampel Surabaya - Fahimatul Ula; Misbakhul Munir; Hanik Faizah (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2021)
The condition of eating places such as street vendors will determine the level of food hygiene, including the water used to wash food utensils. This study aimed to determine the number of microbes and identify Escherichia coli and Salmonella sp. on the water that was used to wash tableware by street vendors around UIN Sunan Ampel Surabaya. Water samples before and after being used to wash tableware were obtained from 4 street vendors. The number of microbes in the sample was tested by the Total Plate Count (TPC) and Most Probable Number (MPN) methods, Escherichia coli was identified using Eosin Methylene Blue Agar (EMB) media, and Salmonella sp. was identified using Salmonella-Shigella agar (SSA) and Triple Sugar Iron agar (TSIA) media. Based on the results of TPC test, the water sample before being used to wash tableware had the lowest and highest values that were 3.0 x 102 Cfu/ml and 9.8 x 105 Cfu/ml, respectively, while the water sample after being used to wash tableware had the lowest and highest values that were 4.0 x 102 Cfu/ml and 3.5 x 105 Cfu/ml, respectively. In the MPN test, the water sample before being used to wash tableware had the lowest and highest values that were 15/100ml and 26 100/ml, respectively, while the water sample after being used to wash tableware had the lowest and highest values that were 72/100 ml and 271/ 100 ml, respectively. Escherichia coli was detected in all samples 1&3 while in sample 2 Escherichia coli was detected in the water before it was detected the genus Enterobacter and in samples 4 the genus Enterobacter was detected and all samples water used to wash tableware of street vendors was positive for Salmonella.